Traditional uses, botanical description, phytochemistry, and pharmacological activities of Phytolacca acinosa: a review - Khalid, Tooba; Chang, Chieh-Wei; Ross, Samir Anis; Naseer, Faiza; Qadeer, Abdul; Chen, Chien-Chin; Rafey, Hafiz Abdul (Frontiers in Pharmacology, 2025)
Background: Phytolacca acinosa is a herbaceous herb that is a member of the Phytolaccaceae family. The plant has a long history of usage in traditional medicine for a variety of ailments including infectious diseases, edema, inflammation, gastric and abdominal distress. The traditional use, phytochemistry and pharmacological properties of Phytolacca acinosa are outlined in this article.Main text: To date, few bioactive molecules have been identified and isolated from the plant such as Phytolacacinoside A, esculentoside H, jaligonic acid and esculentoside B, phytolaccanol and epiacetylaleuritolic acid, esculentoside A, esculentoside C, esculentoside D, esculentoside T, esculentoside S, sitosterol and many more. The literature related some of the reported ethnomedicinal uses of the plant to these compounds found in different parts of the plant.The in-depth knowledge about the significance of Phytolacca acinosa presented in this review may open up opportunities for research development in drug discovery and a better comprehension of the therapeutic advantages of the plant.